2016
DOI: 10.1111/cgf.12840
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Estimation of Energy‐Based Hyperelastic Objects

Abstract: Figure 1: Deformations of real-world objects are nonlinear, anisotropic, and heterogeneous. Our general energy-based model of hyperelasticity allows the estimation of accurate and robust models for diverse real-world examples, including cloth, skin, or internal anatomy. AbstractIn this paper, we present a method to model hyperelasticity that is well suited for representing the nonlinearity of real-world objects, as well as for estimating it from deformation examples. Previous approaches suffer several limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Soft materials of interest in graphics, like cloth, rubber, muscle, and skin, exhibit a strongly nonlinear elastic response when undergoing large deformations. Much previous work in graphics has focused on acquiring nonlinear constitutive models of volumetric soft tissue [1,4] and cloth [2,3] from observed data; their results show that nonlinearity leads to more realistic visual behavior than linear elastic models. Furthermore, Xu et al [10] recently showed that allowing artists to directly specify the nonlinear elastic response of a simulated material enables desirable animation effects to be achieved.…”
Section: Nonlinear Elastic Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soft materials of interest in graphics, like cloth, rubber, muscle, and skin, exhibit a strongly nonlinear elastic response when undergoing large deformations. Much previous work in graphics has focused on acquiring nonlinear constitutive models of volumetric soft tissue [1,4] and cloth [2,3] from observed data; their results show that nonlinearity leads to more realistic visual behavior than linear elastic models. Furthermore, Xu et al [10] recently showed that allowing artists to directly specify the nonlinear elastic response of a simulated material enables desirable animation effects to be achieved.…”
Section: Nonlinear Elastic Modelsmentioning
confidence: 99%
“…An important application of nonlinear constitutive models is the use of data-driven materials acquired from real objects. Unfortunately, with the exception of the recent work of [4], most existing techniques [1,2,3] represent the acquired material as a stress-strain response function, which may not necessarily correspond to a hyperelastic (conservative) material. Finding a hyperelastic model whose stress-strain response best fits a given response function would allow existing databases of acquired nonlinear materials to be used in optimization-based integration techniques such as ours.…”
Section: Convergencementioning
confidence: 99%
See 1 more Smart Citation
“…FEM simulations are greatly in uenced by the speci c strain-stress material relationship, and the damping model. Since the pioneering work of deformable object simulation [Terzopoulos et al 1987], there has been a lot of research on extending the expressive range of materials [Bargteil et al 2007;Irving et al 2004;Müller and Gross 2004], forward design of materials [Li and Barbič 2014;Martin et al 2011;Miguel et al 2016;Schumacher et al 2012;Xu et al 2015b] or material parameter optimizations [Becker and Teschner 2007;Bickel et al 2009;Xu et al 2015a]. However, few publications focused on the design of damping for physically-based simulation.…”
Section: Materials Designmentioning
confidence: 99%
“…We build our damping model on top of the concept of dissipation potential from classical mechanics [GPS14]. This approach parallels the design of elastic deformation models based on energy formulations [XSZB15, MMO16], and same as energy‐based elastic models simplify the enforcement of good elasticity conditions, dissipation potentials simplify the enforcement of good damping conditions. As described in Section 3, we propose a framework for damping models with dissipation potentials based on strain rate.…”
Section: Introductionmentioning
confidence: 99%